Strategy Analysis of Building Sharia Residential Property Business Without Banks (A Case Study of “Semarang Ngaliyan Residence” Syariah Housing in West Semarang) - Millatun Nadzifah; zuhdan ady fataron (ITB AAS INDONESIA Surakarta, 2019)
This article is aimed to analyze how the structure of building a sharia home property business without banks. The most recent alternative housing is housing with the concept of sharia without using national banking mortgages. This study used qualitative methods by examining some credible sources in obtaining the data . The results showed that based on the analysis of the residential property business Ngaliyan Residence has been able to answer 9 points of reference BMC analysis (Business Model Canvas) which includes; Value Propositions, Customer Segments, Channels, Customer Relationships, Key Resources, Key Activities, Key Partnerships, andCost Structure. Service strategy is one of the strategies implemented in Ngaliyan Residence for a market segment applied by Ngaliyan Residence, which in turn can realize customer loyalty .